A Cultural Criminology for Latin America: An Invitation from the South (Delito y Sociedad, 2025)
This article proposes a critical reflection on the need to develop a Latin American cultural criminology capable of addressing the complexity of criminal phenomena in the region from a situated and contextual perspective. Drawing on the contributions of Rosa del Olmo, this article analyzes the current challenges of criminology in Latin America, marked by structural violence, inequality, and the influence of foreign theories. The article reviews the main topics addressed by cultural criminology in the Global North, such as the interrelationship between culture and subcultures, the influence of the media, and social exclusion, and explores Latin American works that converge with this approach. The article argues that a Latin American cultural criminology must be transdisciplinary, rooted in local realities but aware of their global interconnectedness. It highlights examples such as cultural criminology in Brazil and studies that address everyday violence, the media representation of crime, and social exclusion in the region. In conclusion, the importance of building bridges between individual experiences, cultural meanings, and power structures is emphasized, proposing a criminology committed to social justice and capable of responding to the challenges of the 21st century.
Keywords: Cultural Criminology; Latin America; Social justice; criminal phenomena